MiR‐186‐5p suppresses cell migration, invasion, and epithelial mesenchymal transition in bladder cancer by targeting RAB27A/B. Issue 11 (22nd July 2021) - Zhang, Qianjin; Hao, Lin; Shen, Zhiyong; Wang, Fengye; Han, Conghui
Abstract: Bladder cancer (BCa) is a common malignancy in the urinary system. Ras‐related protein Rab‐27A (RAB27A) and Ras‐related protein Rab‐27B (RAB27B) have been verified to be closely related to the development of many tumors. Since the role of both RAB27A and RAB27B in BCa have not been reported, we intended to explore the function and mechanism of RAB27A and RAB27B in BCa development. Reverse transcription quantitative polymerase chain reaction revealed that RAB27A/B showed high expression in BCa tissues and cells. Cell counting kit‐8, wound healing and Transwell assays as well as western blot analyses revealed that silencing RAB27A/B suppressed BCa cell proliferation, migration and invasion as well as the epithelial‐mesenchymal transition (EMT) process. Based on bioinformatics analysis and our experiments, microRNA‐186‐5p (miR‐186‐5p) was found to be the upstream miRNA of RAB27A/B in BCa. MiR‐186‐5p expression was significantly downregulated in BCa cells and tissues. MiR‐186‐5p directly targeted the 3′‐untranslated region (3′‐UTR) of RAB27A/B and downregulated both mRNA and protein levels of RAB27A/B in BCa cells. MiR‐186‐5p overexpression suppressed BCa cell proliferation, migration and invasion as well as the EMT process in vitro and inhibited tumor growth in vivo. Overexpressing RAB27A/B rescued the inhibitory effect of miR‐186‐5p on malignant phenotypes of BCa cells. Furthermore, miR‐186‐5p inactivated the phosphatidylinositol 3‐Kinase (PI3K)/mitogen‐activated protein kinase (MAPK) signaling pathway by downregulating the expression of RAB27A/B, as shown in western blot analysis. Overall, miR‐186‐5p suppressed BCa cell proliferation, migration, invasion and EMT process and inhibited xenograft tumor growth by targeting RAB27A/B to inactivate the PI3K/MAPK signaling.